Relationship of Knowledge, Attitudes, and Family Support with Antenatal Care Visits at UPT Puskesmas Damai, West Kutai Regency - Marissa Oktavilia; Andi Parellangi; Fara Imelda Th. Patty (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the relationship between knowledge, attitudes and family support with antenatal care visits. This type of research is descriptive analytic with cross sectional research design. The population in this study were all pregnant women in the working area of ​​the UPT Puskesmas Damai West Kutai Regency in September - November 2021, totaling 147 people. The sampling technique used was purposive sampling with a total sample of 60 respondents. Data analysis technique used the chi square test. Based on the research results obtained, it can be concluded that there is a relationship between knowledge and ANC visits (p-value = 0.000; OR = 3.07 – 219.7), attitude and ANC visits (p-value = 0.020 ; OR = 1.08 – 66.5), and family support with ANC visits (p-value = 0.015 ; OR = 1.10 – 103).